(3GdCMcGe GdcHQis
(3ChdgG (B:s
(3cJGH GdCeQGV hGdYjGOI s
(3BNQgG (B:s
(3abdJ deYGhjI cja cGf JQLjYg bGd KdGK eQGJ ced GdSaQ GdNGeS HMeO Gddg hYhfg hfUQg jJdhg Ef TGA Gddg aj Chd GdSaQ GdSGOS HGH GdLgQ HGdbQBf hJQJjdg hcja ojbQC s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdcj(B) s
Keywords: (3Gdabg GdeGdcjs